2007
DOI: 10.1136/ard.2007.073502
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorycholine moiety of the filarial nematode immunomodulator ES-62 is responsible for its anti-inflammatory action in arthritis

Abstract: Objective: In countries where parasitic infections are endemic, autoimmune disease is relatively rare, leading to the hypothesis that parasite-derived immunomodulators may protect against its development. Consistent with this, we have previously demonstrated that ES-62, a 62 kDa phosphorylcholine (PC)-containing glycoprotein that is secreted by filarial nematodes, can exert antiinflammatory action in the murine collagen-induced arthritis (CIA) model and human rheumatoid arthritisderived synovial tissue culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 23 publications
6
85
1
1
Order By: Relevance
“…However, in areas of the world where helminth infections are endemic, rates of autoimmune diseases such as RA remain low, leading to the hypothesis that certain helminth infections may protect against the development of autoimmunity (1). In support of this theory, we have previously shown that ES-62, a phosphorylcholine-containing glycoprotein secreted by the filarial nematode Acanthocheilonema viteae, has broad immunomodulatory activities and can exert powerful antiinflammatory action in the mouse collagen-induced arthritis (CIA) model of RA (2,3).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…However, in areas of the world where helminth infections are endemic, rates of autoimmune diseases such as RA remain low, leading to the hypothesis that certain helminth infections may protect against the development of autoimmunity (1). In support of this theory, we have previously shown that ES-62, a phosphorylcholine-containing glycoprotein secreted by the filarial nematode Acanthocheilonema viteae, has broad immunomodulatory activities and can exert powerful antiinflammatory action in the mouse collagen-induced arthritis (CIA) model of RA (2,3).…”
mentioning
confidence: 84%
“…CIA was induced in 8-10-week-old male DBA/1 mice (Harlan Olac) on day 0 by intradermal immunization with bovine type II collagen (MD Biosciences) in Freund's complete adjuvant (CFA). Mice were treated with purified endotoxin-free ES-62 (2 g/dose) or phosphate buffered saline (PBS) subcutaneously on days Ϫ2, 0, and 21 (2,3), and cells were recovered from the joints as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects were associated with decreased TNF-a, IFN-c, and IL-6, and increased IL-10 release. Interestingly, the ES-62-mediated suppression of CIA, as well as the reduction in IFN-c levels, was dependent on a phosphorylcholine (PC) moiety (14), which is linked to N-glycans of this glycoprotein (15).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Whereas mature DC incubated with LPS induce more IFN-c and less IL-4 than control cells, incubation with ES-62 had the opposite effect. This effect was dependent on the PC moiety since PC coupled to OVA could mimic the effect, whereas recombinant ES-62 had no antiinflammatory effect (14). Furthermore, deglycosylation of extracts from the free-living nematode Caenorhabditis elegans as well as the parasitic nematode Brugia malay (52) reduced the Th2-polarizing capacity of these nematodes compared with the control extracts.…”
Section: Helminth Glycans and Their Role In Th2 Polarization And Antimentioning
confidence: 99%